Single crystal forms induced diverse interface structures in TiO2 (B)/anatase dual-phase nanocomposites. Issue 12 (29th February 2016) - Sun, Jie; Lei, Yimin; Liu, Hongwei; Ringer, S. P.; Liu, Zongwen
Abstract : Two types of TiO2 (B) single crystal forms (SCF) and the induced TiO2 (B)/anatase interfaces with different orientation relationships are investigated by TEM. The dominated (001